Influence and interference in foreign elections - Baines, Paul R.; Jones, Nigel (Taylor and Francis, 2018)
The use of influence or interference activities by one country to change the tide of elections in another has recently gained prominence due to alleged Russian influence in the 2016 US presidential election and the 2017 French presidential election. In this article, Paul Baines and Nigel Jones chart the evolution of influence and interference in foreign elections. With the rise of its modern digital form, they consider whether it is acceptable as a norm in international relations, or a violation.